2004
DOI: 10.1063/1.1695618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of argon additive on H− density and temperature in volume negative ion source

Abstract: Various plasma parameters were measured for several hydrogen-argon mixtures in the multicusp H Ϫ ion source Camembert III, equipped with tantalum filaments. The density and the temperature of electrons were measured with the Langmuir probe situated in the center of the source and associated with the photodetachment diagnostics. The two-laser photodetachment diagnostics was used to obtain the temperatures of the two negative ion populations. At low hydrogen pressure ͑0.8 mTorr͒ a small concentration of argon ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…[112][113][114][115][116][117] This concept was earlier predicted by Hiskes et al 118 Several research efforts were made to study the effect on the H À ion density by mixing argon and other inert gases to hydrogen. [119][120][121][122] Work on the performance improvement of large RF driven hydrogen negative ion sources for fusion integrated the idea of mixing argon or other inert gases to hydrogen and was initiated at IPP and described in 1999 by Speth et al 123 In this source, the RF antenna was located near the back plate. It was found that the negative ion yield increased with pressure but saturated with rf power.…”
Section: Volume Negative Ion Sources For Fusion Applicationsmentioning
confidence: 99%
“…[112][113][114][115][116][117] This concept was earlier predicted by Hiskes et al 118 Several research efforts were made to study the effect on the H À ion density by mixing argon and other inert gases to hydrogen. [119][120][121][122] Work on the performance improvement of large RF driven hydrogen negative ion sources for fusion integrated the idea of mixing argon or other inert gases to hydrogen and was initiated at IPP and described in 1999 by Speth et al 123 In this source, the RF antenna was located near the back plate. It was found that the negative ion yield increased with pressure but saturated with rf power.…”
Section: Volume Negative Ion Sources For Fusion Applicationsmentioning
confidence: 99%
“…To the best of our knowledge, the most indicative reports on the application of this process are the Refs. [4][5][6][7][8][9], concerning filament-driven sources. More recently, Kado et al [10] proposed a novel and simple method to measure thermal and flow velocities of negative ions by making use of the photodetachment technique in a steady-state linear divertor/edge plasma simulator MAP (material and plasma)-II.…”
Section: Introductionmentioning
confidence: 99%
“…Systems with higher frequencies have also been used. Electron cyclotron resonance ͑ECR͒ heating 10 with modified standard sources 11,12 and seven small ECR systems 13 in a multicusp source were tested. Microwave sources were used and even tandem combinations of a microwave source with a multicusp source 14 were tried.…”
Section: The Discharge Chambermentioning
confidence: 99%